Oxford Handbooks Online 2017
DOI: 10.1093/oxfordhb/9780199399314.013.7
|View full text |Cite
|
Sign up to set email alerts
|

Hope Measurement

Abstract: This chapter covers the multiple measures currently used to assess hope theory. Hope, as theorized by Snyder and colleagues, was originally determined to be a global construct measuring agency and pathways toward goal attainment. Using much of the original theory, hope research has expanded, resulting in multiple measures across different applications and domains. By exploring the context specificity, these scales have been shown to consistently predict outcomes across differing domains, supporting the reliabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Although several studies have demonstrated that trait hope has benefits for parents, domain-specific measures of hope may be more sensitive measures of change resulting from hope-based interventions (Rose & Seiben, 2018). The results of this study provide initial support for the reliability and validity of the HFPS, which measures domain-specific hope for parenting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies have demonstrated that trait hope has benefits for parents, domain-specific measures of hope may be more sensitive measures of change resulting from hope-based interventions (Rose & Seiben, 2018). The results of this study provide initial support for the reliability and validity of the HFPS, which measures domain-specific hope for parenting.…”
Section: Discussionmentioning
confidence: 99%
“…Rose and Sieben (2018) suggested that domain-specific measures of hope may be more sensitive measures of change resulting from hope-based interventions and encouraged additional research into their utility. Sympson’s (1999) Domain-Specific Hope Scale was developed to examine hope within a variety of interpersonal and achievement-oriented contexts including relationships, work, and academics.…”
Section: Hopementioning
confidence: 99%
“…In the current sample, a coefficient alpha of .75 was obtained for agency and .69 for pathways. Support for construct validity for the Hope Scale has been shown through positive correlations with measures of optimism, self-actualization, and self-esteem, and negative correlations with self-consciousness, hopelessness, depression, and suicidal ideation (for a full review of the Adult Hope Scale and its psychometric properties, see Rose & Sieben, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The same could be said of Snyder's Adult Dispositional Hope Scale (Snyder et al., 1996). For recent discussions of hope as a psychological construct, see Rose and Sieben (2017), Gallagher, D'Souza, and Richardson (2020).…”
mentioning
confidence: 99%